2015
DOI: 10.1007/s40725-015-0018-4
|View full text |Cite
|
Sign up to set email alerts
|

Mangrove Response to Environmental Changes Predicted Under Varying Climates: Case Studies from Australia

Abstract: Over the past few decades, many of the world's mangrove forests have experienced significant change, which can be attributed to human activities and also natural causes. However, a component may also be due to factors that are commonly associated with anthropogenic climate change including higher air temperatures, variations in rainfall, increases in storm frequencies and intensities, and rising sea levels. The expected responses of mangrove to these drivers include changes in extent (latitudinal, seaward and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 113 publications
(102 reference statements)
0
31
0
Order By: Relevance
“…Although the majority of mangroves were able to recover, the complete burial of many pneumatophores resulted in mass mortality in the following year (Hopley, 1974). Similarly, following major flooding in January 2011, 92% of the mangroves along 76 km of the Brisbane River experienced mortality as a result of inundation and erosion (Asbridge et al, 2015;Dowling, 2012). Following Hurricane Andrew in Florida in 1992, erosion of sediments (by an average of 2-3 cm (Cahoon et al, 2003)) led to the uprooting of trees which further exposed previously protected land behind the forest to wind and wave action (Doyle et al, 1995;Swiadek, 1997).…”
Section: Erosionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the majority of mangroves were able to recover, the complete burial of many pneumatophores resulted in mass mortality in the following year (Hopley, 1974). Similarly, following major flooding in January 2011, 92% of the mangroves along 76 km of the Brisbane River experienced mortality as a result of inundation and erosion (Asbridge et al, 2015;Dowling, 2012). Following Hurricane Andrew in Florida in 1992, erosion of sediments (by an average of 2-3 cm (Cahoon et al, 2003)) led to the uprooting of trees which further exposed previously protected land behind the forest to wind and wave action (Doyle et al, 1995;Swiadek, 1997).…”
Section: Erosionmentioning
confidence: 99%
“…Mangrove loss and gain in extent and condition are also associated with natural events (e.g., intense storms, tsunamis) and processes (e.g., changing sea levels, ocean circulations climate; (Asbridge, Lucas, Accad, & Dowling, 2015;Asbridge & Lucas, 2016;Gilman, Ellison, Duke, & Field, 2008). Increasingly, natural processes are being exacerbated by drivers associated with climatic changes, including those linked with human activities (McKee, Rogers, & Saintilan, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…, , Asbridge et al. ). Unfortunately, a lack of relevant and easily accessible climate and/or ecological data has meant that many of these relationships have not been fully tested or quantified.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the tremendous ecological and societal value of mangrove forests, the influence of climatic drivers on mangrove forest distribution, structure, and function has not been well quantified in many parts of the world. The mangrove literature contains many valuable observations and well-articulated hypotheses regarding the influence of temperature and rainfall regimes on the distribution, abundance, and diversity of mangrove forests (e.g., Davis 1940, Lugo and Patterson-Zucca 1977, West 1977, Woodroffe and Grindrod 1991, Duke et al 1998, Saenger 2002, Ross et al 2009, Saintilan et al 2009, 2014, Asbridge et al 2015. Unfortunately, a lack of relevant and easily accessible climate and/or ecological data has meant that many of these relationships have not been fully tested or quantified.…”
mentioning
confidence: 99%
“…This system has a high productivity and decomposition rate, and plays an important role in species survival and in the carbon balance in the coastal zone [1][2][3][4][5][6][7]. Over the past few decades, the global mangrove forests have undergone significant changes on distributive pattern and area, caused by a variety of factors including rising temperatures, changes in precipitation patterns, increased frequency and intensity of storms and sea level rise [8]. Some studies have shown that if the sea level rise is sufficiently slow and there are suitable area and environmental conditions, the mangrove forests are able to adapt gradually [1].…”
Section: Introductionmentioning
confidence: 99%